Factor endowments, wage growth, and changing food self-sufficiency: Evidence from country-level panel data - Otsuka, Keijiro; Liu, Yanyan; Yamauchi, Futoshi (International Food Policy Research Institute, 2013)
Asian countries have witnessed a sharp increase in real wage as a result of rapid economic growth and structural transformation in recent years. Using a country level panel data from 1980 to 2010, this paper examines the effects of real wage increase on Asian agriculture that traditionally used family labor intensively on small farms. The empirical evidence supports our hypothesis that an increase in real wages, along with absorptions of labor into nonagricultural sectors, has been inducing the substitution of labor by machines in agriculture. However, this process is less successful in the countries that are constrained by their small operational land sizes, resulting in lowered land productivity. We also demonstrated that dynamic changes in yield are an important determinant of food self-sufficiency ratio.